Symphony No. 7 by Krzysztof Meyer – strategy of building the form, expressivity of the work - Podhajski, Marek (Katedra Muzykologii, Wydawnictwo Naukowe PTPN, Wydawnictwo Naukowe UAM, 2011)
The article brings closer the formal and expressive properties of the 7th Symphony by Krzysztof Meyer, composed in the years 2002/2003. Meyer distinguishes several specific features that should be taken into consideration during the process of composing.These include: the capacity to adapt, the limitation of soundinformation transferred onto the listener, and a division of the form into integrant phases. The capacity to ‘adapt’ occurs through opposing emotional states connected with the reception of music: remembering, familiarising, and becoming used to a certain property of the musical progress – surprise that emerges with the appearance of a change. The surprise effect is a strong reaction, and one that is sought after for the purpose of maintaining a high level of the listener’s engagement in the reception process of music. The need to ‘limit the sound-information’ that the composer transfers onto the listener allows the latter to take note of it and remember it. An information overload leads to a sense of disorientation, being lost, and consequently discouragement from active listening. Finally, ‘the significance of the structural elements of the form’ is considered. In his conclusion, Meyer presents a model of musical form as a progress based on phases unfolding in time. The composer outlines the following phases: the initial phase, the essential phase, the transitional phase, the phase of particular importance, and the final phase. However, he warns against literal and orthodox understanding of his concept. ‘Meyer’s fundamental aim is ‘to lead’ the listener and not to overstretch their perceptive capabilities. A ‘planned spontaneity’ is the purpose’.‘All the symphonies by Meyer, both early and recent, were shaped in the same manner. The process is at the forefront: build-up, development, clashing collisions, conflict of contrasting elements’. The 7th Symphony is also built according to similar constructional principles. What distinguishes it from the earlier works in this genre is connected with the expressivity of the work. The composer notes: ‘The symphony evolves according to musical laws par excellence, but not without admitting some thoughts about myself in metaphorical categories, because, after all, the subtitle ‘Sinfonia del tempo che passa’ – Symphony of the Passing Time – was not chosen accidentally’. Thus it is a tale about one of the most fundamental existential experiences of every human being: the passing. This is suggested by the emotional aura of the music, the subtitle that the work was given, and references to emphatic rhetoricalmusical figures known from the Baroque period. As Thomas Wesselman wrote: ‘The subtitle Symphony of the Passing Time clearly invites the assigning of a retrospective character to this opus no. 97’. ‘It is true that the composer has never commented on the subject, but the justification of the suspicion seems to be confirmed by the expressivity of the final movement (molto lento), which, in a way, is a statement filled with peace and tranquillity made by a human being with years of experience behind him. In any case, it suffices to compare this symphony with its two predecessors, i.e. the 5th,full of energy and scored for strings, and the dramatic 6th written as a reaction to the introduction of the martial law in Poland; one has a sensation that a moment of reflection (pondering over life’s end?) plays a special role in the 7th’.
Keywords: 20th century; Polish composers; Krzysztof Meyer; Symphony no. 7; form; expressivity of the work